Morphological and biochemical evaluation of effects of myrtus communis l. Extract on heart and aorta in high fat-diet induced obese rats - ŞEN, ALİ; ERCAN, FERİHA (My University, 2023)
Objectives: The purpose of this study was to examine the protective effects of Myrtus communis L. (MC) extract on high fat-diet (HFD) induced heart and aorta damage by evaluating oxidative stress and the endothelial nitric oxide system (eNOS). Materials and Methods: Wistar albino male rats were divided into 3 groups (n=7) as control, HFD and HFD+MC. Rats in HFD and HFD+MC groups were HFD fed for 16 weeks and in the last 4 weeks saline or MC (100 mg/kg) was administered orally (5 days/week). Triglyceride, cholesterol and HDL were estimated in blood serum. Tissue oxidative stress and inflammatory parameters were evaluated biochemically. Tissues morphologies, eNOS, inducible NOS (iNOS) and NADPH oxidase-2 (NOX-2)-immunopositive and apoptotic cells were evaluated histologically. Results: Altered serum lipid profiles, degenerated heart and aorta morphology, increased malondialdehyde, 8‐hydroxy‐2‐deoxyguanosine, tumor necrosis factor-alpha, monocyte chemoattractant protein-1 and myeloperoxidase levels and iNOS, NOX-2 immunopositive and apoptotic cells, decreased NO levels, eNOS-immunopositive cells in both tissues were observed in HFD group. All these parameters improved in HFD+MC group. Conclusion: This study revealed that HFD-induced obesity increased iNOS activation and oxidative stress in both tissues. MC regulated oxidant/antioxidant had balanced thus preventing heart and aorta damage via eNOS involvement.
Keywords: Tıp; Histoloji-Embriyoloji; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Histology and Embryology; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Moleküler Biyoloji ve Genetik; TIP, GENEL & DAHİLİ; HÜCRE BİYOLOJİSİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; MOLECULAR BIOLOGY & GENETICS; MEDICINE, GENERAL & INTERNAL; CELL BIOLOGY; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Hücre Biyolojisi; Yaşam Bilimleri; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Cell Biology; Life Sciences